Investigation of bimetals compound with the aim to increase of equipment reliability for complex gas preparation - Makeeva, H.S.; Frolov, Ya.V.; Stolbchenko, M.Y.; Grydin, O.Y.; Schaper, M.; Makeev, S.Yu. (Геотехнічна механіка, 2017)
This article is devoted to the investigation of technical process of reinforcement of aluminum sheets with wire for increasing equipment reliability for complex gas preparation. Reduction of operating coalmines forces to give more attention to gas and gas-condensate deposits. Статтю присвячено дослідженню технологічного процесу армування алюмінієвих листів дротом для підвищення надійності обладнання для комплексної підготовки газу. Скорочення працюючих вугільних шахт, змушує більше уваги приділяти газовим і газоконденсатним родовищам. Статья посвящена исследованию технологического процесса армирования алюминиевых листов проволокой для повышения надежности оборудования для комплексной подготовки газа. Сокращение работающих угольных шахт, вынуждает больше внимания уделять газовым и газоконденсатным месторождениям.